Owner perceptions and management of stereotypic behaviors in four horse breeds in Costa Rica - Arias-Esquivel, Ana Margarita (2020)
Introduction. There is little information about stereotypic behaviors in stock-type sport horses and paso horses in Costa Rica. The lack of knowledge regarding stereotypic behaviors, such as cribbing, weaving, and stall walking in horses, affects their welfare. Objective. The objective of this study was to monitor the status of stereotypic behaviors and the management reported by owners of horses registered in ACRICAMDE and ASCACOPA in Costa Rica.Materials and methods. A cross-sectional survey was conducted from June through September 2018 in Costa Rica to gather information on horse behavior and current management practices of 552 horses of the breeds Quarter Mille, Appaloosa, American Paint Horses and Costa Rica Paso. The database collected was analyzed using descriptive statistics. Results. Almost half of the horse owners (48.4 %) reported stereotypic behaviors, being cribbing the most observed (86.2 %), followed by stall walking (24.1 %) and weaving (13.8 %). Most owners and managers (89.7 %) have tried to stop horses from performing stereotypic behaviors with anti-cribbing collars and by increasing social contact with other horses as the most common approaches. Fewer hours of grazing were reported (2 or less, or none) while there were horses without access to pasture (35.7 %). Conclusion. Horse owners of the breeds included in this study lacked knowledge of stereotypic behaviors. In order to improve management of these behaviors, more training is required to avoid further complexities under the current conditions.